Increased migration of cord blood-derived CD34 + cells, as compared to bone marrow and mobilized peripheral blood CD34 + cells across uncoated or fibronectin-coated filters - Voermans, Carlijn; Gerritsen, Winald R.; von dem Borne, Albert E.G.Kr; van der Schoot, C.Ellen (Experimental hematology, 1999)
Hematopoietic progenitor cells (CD34 + cells) migrate to the bone marrow after reinfusion into peripheral veins. Stromal cell-derived factor-1 (SDF-1) is a chemokine produced by bone marrow stromal cells that induces migration of CD34 + cells. In this study we compared spontaneous and SDF-1-induced migration of CD34 + cells from bone marrow (BM), peripheral blood (PB), and cord blood (CB) across Transwell filters. Under all circumstances, CB CD34 + cells showed significantly more migration than did BM or PB CD34 + cells. SDF-1 induced migration of BM CD34 + cells was higher than that of PB CD34 + cells, possibly due to differences in sensitivity towards SDF-1. Indeed, PB CD34 + cells showed a significantly lower expression of the receptor for SDF-1 (CXCR-4) than did BM and CB CD34 + cells. The sensitivity to SDF-1, as measured by migration towards different concentrations of SDF-1, was identical for BM and CB-derived CD34 + cells and correlated with their equal CXCR-4 receptor expression. Coating of the filters with the extracellular matrix protein fibronectin (FN) strongly enhanced the SDF-1-induced migration of PB CD34 + cells (2.5 times) and of BM CD34 + cells (1.5 times). SDF-1 induced migration of PB CD34 + cells over FN-coated filters was blocked by antibodies against β 1 integrins. Subsequently, analysis was performed to determine whether SDF-1 preferentially promoted migration of subsets of CD34 + cells. Actively cycling CD34 + cells, which were present in BM (14%) but hardly in PB (2.2%) or CB (1.2%), were found to migrate preferentially towards SDF-1. In the input, 14% ± 2.5% of the BM CD34 +cells were in G 2/M and S phase, whereas in the migrated fraction 20% ± 5.7% of the cells were actively cycling ( p < 0.05). We did not observe preferential migration of phenotypically recognizable primitive CD34 +subsets, despite the fact that CB CD34 + cells are thought to contain a higher percentage of immature subsets. In conclusion, the relatively lower migration of PB CD34 + cells seems to be due to a lower sensitivity towards SDF-1, and the higher migrational capacity of CB CD34 + cells, in comparison to BM and PB CD34 +cells, seems to have an as yet unknown intrinsic cause. The increased migration of CB CD34 + cells may favor homing of these cells to the bone marrow, which might reduce the number of cells required for hematological reconstitution after transplantation.